2003
DOI: 10.1080/00223980309600607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peers and Families in Predicting the Loneliness Level of Adolescents

Abstract: The authors investigated the relative contribution of peer relations, family structure, and demographic variables in predicting loneliness in adolescents. Ninth-grade high school students (N = 756) from 8 different schools representing various socioeconomic status in Ankara, Turkey, completed the UCLA Loneliness Scale (D. Russell, L. A. Peplau, & M. L. Ferguson, 1978), the Family Structure Assessing Instrument (A. Gülerce, 1996), and an author-constructed questionnaire involving demographic information and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
9
26
0
5
Order By: Relevance
“…Students who reported their family environment to be high coherent reported lower loneliness. Earlier studies also revealed the importance of a coherent family environment in the development of loneliness (Brage et al, 1994;Girgin, 2009;Uruk & Demir, 2003). This result is consistent with the findings of Hojat (1982), who found that adolescents who have problems with their parents were more likely to experience loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…Students who reported their family environment to be high coherent reported lower loneliness. Earlier studies also revealed the importance of a coherent family environment in the development of loneliness (Brage et al, 1994;Girgin, 2009;Uruk & Demir, 2003). This result is consistent with the findings of Hojat (1982), who found that adolescents who have problems with their parents were more likely to experience loneliness.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature there are studies that have reached similar results based on the variables of college year (Atlı & Keldal, 2015;Baran et al, 2015;Certel, Yakut, Yakut & Gülsün, 2016), parent's education level (Uruk & Demir, 2003;Baran et al, 2015), and number of siblings (Uruk & Demir, 2003;Baran et al, 2015).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 67%
“…According to several studies (e.g., de Jong Gierveld & Havens, 2004;Killeen, 1998;Saari, 2009), loneliness is a socio-political question, and therefore, communal methods, distribution of information, and holistic culture of caring should be considered salient societal means of preventing problems such as loneliness. Although it is possible to arrange expensive and large societal and educational interventions to prevent loneliness (see e.g., Masi, Chen, Hawkley, & Cacioppo, 2011;VanderWeele et al, 2011), often the roots of loneliness can be found in childhood, friendships, and families (Uruk & Demir, 2003). Therefore, we want to spend a moment discussing the role of peer support.…”
Section: Resultsmentioning
confidence: 99%